Evaluation of AAPM Reports 204 and 220: Estimation of effective diameter, water‐equivalent diameter, and ellipticity ratios for chest, abdomen, pelvis, and head CT scans. (27th November 2017) - Burton, Christiane S.; Szczykutowicz, Timothy P.
Abstract: Purpose: To confirm AAPM Reports 204/220 and provide data for the future expansion of these reports by: (a) presenting the first large‐scale confirmation of the reports using clinical data, (b) providing the community with size surrogate data for the head region which was not provided in the original reports, and additionally providing the measurements of patient ellipticity ratio for different body regions. Method: A total of 884 routine scans were included in our analysis including data from the head, thorax, abdomen, and pelvis for adults and pediatrics. We calculated the ellipticity ratio and all of the size surrogates presented in AAPM Reports 204/220. We correlated the purely geometric‐based metrics with the "gold standard" water‐equivalent diameter (DW ). Results: Our results and AAPM Reports 204/220 agree within our data's 95% confidence intervals. Outliers to the AAPM reports' methods were caused by excess gas in the GI tract, exceptionally low BMI, and cranial metaphyseal dysplasia. For the head, we show lower correlation (R 2 = 0.812) between effective diameter and DW relative to other body regions. The ellipticity ratio of the shoulder region was the highest at 2.28 ± 0.22 and the head the smallest at 0.85 ± 0.08. The abdomen pelvis, chest, thorax, and abdomen regions all had ellipticity values near 1.5. Conclusion: We confirmed AAPM reports 204/220 using clinical data and identified patient conditions causing discrepancies. We presented new size surrogate data for the head region and for the first time presented ellipticity data for all regions. Future automatic exposure control characterization should include ellipticity information.